Analysis of determining factors for stunting events in Petang District, Badung Regency - Dewi, Ni Komang Sukma Candra; Marhaeni, A.A.I.N. (Journal of Economics and Business Letters, 2024)
This study aims to analyze simultaneously and partially the effect of family income, maternal double burden, age at first marriage, and maternal education level on the incidence of stunting in Petang District, Badung Regency. Also, it analyzes the role of maternal education level in moderating the influence of age at first marriage on the incidence of stunting in Petang District, Badung Regency. The sample for this research was determined using the Simple Random Sampling method with a total of 60 respondents. The data collection methods used were observation, structured interviews, and in-depth interviews. Data analysis was carried out using moderated regression analysis. The results of the analysis concluded that family income, maternal double burden, age at first marriage, and maternal education level simultaneously had a significant effect on the incidence of stunting in Petang District. Family income, Age at first marriage, and maternal double burden has a negative and significant effect on the incidence of stunting in Petang District. Maternal Double Burden has a positive and significant effect on the incidence of stunting in Petang District. Maternal education acts as a pseudo-moderating variable that strengthens the influence of age at first marriage on the incidence of stunting in Petang District.